The Effect of Language Sample Elicitation Context on Complex Syntax Use and Productivity in Preschool-Age Children Who Are Deaf and Hard of Hearing. - Cowan, Tiana M.; Lund, Emily; Werfel, Krystal (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Speech-language pathologists tailor language sample elicitation methods to the goals of the assessment and the needs of each child. In school-age children, narrative retell and expository contexts elicit more complex language than conversational contexts. However, the impact of elicitation context on younger children has been less examined. This study examined how conversational, expository, and narrative retell contexts influence productivity and complex syntax in preschool-age children who are deaf and hard of hearing (DHH) compared to peers with typical hearing (CTH). Method: This secondary analysis used data from Werfel et al. (2021). Participants were sixty-nine 4-year-old English-speaking children in three groups: DHH, age-matched peers (CTH-Age), and language-matched peers (CTH-Lang). Amplification type varied among participants who were DHH and included cochlear implants, hearing aids, and bone-anchored hearing aids. All participants communicated with spoken English and had limited exposure to sign language. Language samples were collected using Hadley's (1998) protocol, segmented by elicitation context, and analyzed for productivity (number of utterances, mean length of utterance in morphemes [MLUm]) and complex syntax use (proportion of complex syntax attempts). Generalized linear mixed models examined the effects of group and context on performance. Results: All groups produced significantly more utterances in conversational contexts than in expository discourse or narrative retell. After accounting for the proportion of utterances per context, all groups produced utterances with significantly higher MLUm values and significantly more complex syntax attempts in expository discourse than in conversation. A similar, although nonsignificant, trend was observed for narrative retell. Conclusions: Elicitation context influences productivity and complex syntax use in preschool-age children with and without hearing loss. Findings support the inclusion of varied contexts in clinical language sampling to match specific assessment goals, with expository and narrative retell contexts offering valuable opportunities to elicit complex syntax in preschool-age children.